CrimeSolutions: The evidence-based guide for justice agencies in search of practices and programs that really work. (Corrections Today)
The article focuses on the role of U.S.-based National Institute of Justice's CrimeSolutions, a evidence-based online resource for identifying and rating programs and practices in criminal justice system. It mentions institute's Program evaluation methods, a science-based program and practice innovations to help justice agencies. It also mentions benefits of the program such as reduce crime and delinquency, respond to victimization, and Improve justice systems.